Elastic behavior of anisotropic coatings sputter-deposited at oblique incidence. (1st February 2021) - Zgheib, Elia; Alhussein, Akram; Slim, Mohamed Fares; Khalil, Khaled; François, Manuel
Highlights: An enhanced relation allowing the determination of the elasticity constants of anisotropic coatings was developed. Determination of the elasticity constants of Ti thin films deposited using Glancing Angle Deposition (GLAD). Characterization of Ti thin films sputter-deposited at various polar incidence angles. Microcolumns and fiber tilt angles lie at different glancing angles in the deposition plane. Correlation between mechanical properties, morphology, crystalline structure and texture of as-deposited films. Abstract: In this work, the elasticity constants of anisotropic thin films were determined using a model developed specifically in order to use the Impulse Excitation Technique (IET). The model is based on the lamination theory and was validated with a finite element analysis. The IET was used in flexural and torsional vibration modes in order to determine the Young's and shear moduli of coatings. The anisotropic behavior was evaluated for titanium thin films deposited by magnetron sputtering at Glancing Angle Deposition (GLAD) on glass substrates and silicon wafers. The elastic response was examined for three different glancing angles and the presence of in-plane anisotropy of the film was noticed from the measured elasticity constants. The difference between conventional and GLAD sputtering was evaluated in terms of microstructure, texture evolution and elastic properties. The influence of the film porosity on the elasticity constants was investigated. Nanoindentation measurements were performed in order to evaluate the effect of the glancing angle on the hardness and the reduced modulus. The results revealed that the elasticity constants of the titanium thin film were mostly affected by the glancing angle and they decreased when the glancing angle increased. The same effect was noticed for the film hardness and reduced modulus. Upon increasing the glancing angle, the film anisotropy was increased owing to different factors, among which the non-standard columnar growth and the inclined crystallites toward the vapor flux direction. Graphical abstract: Image, graphical abstract